Green Synthesis of Silver Nanoparticles using Lantana camara Fresh Leaf Extract for Qualitative Detection of Hg2+, Cu2+, Pb2+, and Mn2+ in Aqueous Solution - Henry Fonda Aritonang; Talita Kojong; Harry Koleangan; Audy Denny Wuntu (Universitas Gadjah Mada, 2021)
This research was focused on the discovery of new environmentally friendly sensors based on nanoscale materials whose main purpose was to detect the presence of heavy metals in aqueous solutions. The environmentally friendly extracellular biosynthetic technique was applied to produce silver nanoparticles (AgNps). The reducing agents used were distilled water and ethanol extract obtained from fresh leaves of Lantana camara. The silver-containing extracts (Ag-extract) were then used to detect the presence of Hg2+, Cu2+, Pb2+, and Mn2+ in aqueous solutions by the colorimetric method using UV-visible spectroscopy. The colloidal synthesis of AgNPs was then monitored by the same method. The spectrum obtained showed peaks between 430 and 450 nm according to the Plasmon absorbance of AgNP. AgNPs' size and shape were characterized using the Transmission Electron Microscopy (TEM) technique, which showed the average size varies from 1.6 to 25 nm. The colorimetric data showed that Ag-extract, both of distilled water or ethanol solvents, was the best for detecting the presence of Hg2+ followed by Mn2+. On the other hand, Ag-extract in distilled water cannot detect Cu2+, Pb2+, and Mn2+ ions, while almost all Ag-extracts in ethanol solvents could identify the presence of these metals.